Correlation between Studentsâ Learning Motivation and Writing Achievement at Fourth Semester of English Department Lambung Mangkurat University Banjarmasin. - Apriani, Rini Asrida (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
Learning is very important in developing language skill especially in learning English. One of many factors that influence in learning is motivation. Motivation is in ourselves as intention, hope, and aim that we want to reach include in writing. The aim of this research is to find out the correlation between studentsâ learning motivation and writing achievement. The researcher uses the correlative method. The variables of this research are studentsâ learning motivation and writing achievement. The researcher uses cluster random sampling with the total sample 47 students at fourth semester English Department Lambung Mangkurat University Banjarmasin, the instrument used was the questionnaire about motivation and writing test. To analyze the data, the researcher uses Pearson Product Moment Formula and Statistical Package for Social Sciences (SPSS) version 16.0 windows. The researcher has found the result of the research has a significant coefficient correlation between studentsâ learning motivation and writing achievement and the level is low. Based on the result the researcher suggests that the students need to study and practice more to improve their motivation and writing. It is also suggested to other researchers who are interested in the same topic to use more various instruments in conducting the research.